1988
DOI: 10.1002/eji.1830180110
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria‐reactive Lyt‐2+ T cell lines

Abstract: The biological activities of mycobacteria-reactive Lyt-2+ T cells were characterized in vitro. T cells from mice immunized with killed Mycobacterium tuberculosis or viable M. bovis were restimulated in vitro and cloned under limiting dilution conditions. Several L3T4-Lyt-2+ T cell lines, some of them KJ16+, were established. These T cell lines were capable of lysing mycobacteria-primed macrophages in an antigen-specific way. The cytolytic activity of some T cell lines was found to be class I restricted, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(91 citation statements)
references
References 49 publications
2
89
0
Order By: Relevance
“…Apart from the ability to make cytokines, CD8 ϩ T cells may also function as CTLs; the development of CD8 ϩ CTLs during acute murine tuberculosis has been documented (17,24,33,35,36,39). We demonstrated that, 3 weeks postchallenge, the lungs of memory mice contained CD8…”
Section: Cytotoxic Function Of Memory Cd8 ؉ T Cells Previously We Dmentioning
confidence: 84%
“…Apart from the ability to make cytokines, CD8 ϩ T cells may also function as CTLs; the development of CD8 ϩ CTLs during acute murine tuberculosis has been documented (17,24,33,35,36,39). We demonstrated that, 3 weeks postchallenge, the lungs of memory mice contained CD8…”
Section: Cytotoxic Function Of Memory Cd8 ؉ T Cells Previously We Dmentioning
confidence: 84%
“…monocytogenes is the only pathogen known to induce H2-M3-restricted T cells and it will be of great interest to determine whether other bacterial pathogens can do so. Early studies identified apparently MHC-unrestricted CD8 ϩ T cell responses during infection of mice with Mycobacterium bovis bacille Calmette Guérin (33), which probably reflects restriction by a nonpolymorphic presenting molecule such as H2-M3. The ability of H2-M3 to present Ag via both conventional (TAP-dependent) and unconventional (TAP-independent) processing pathways suggests that it may be particularly well suited for presentation of Ag derived from vacuolar bacterial pathogens such as Mycobacterium tuberculosis or Salmonella typhimurium.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear how these cells are protective. One possibility is that the cytotoxic T cells are needed to release bacteria from safe havens inside ineffective macrophages so that they can be phagocytosed by fresh, fully activated monocytes or macrophages (7). Alternatively, studies with human peripheral blood cells in vitro have indicated that lysis of infected macrophages by antigen-specific T cells can directly result in death of the bacteria (17,22).…”
mentioning
confidence: 99%